Needs Analysis of Redox Reaction E-Module Teaching Material Based on PjBL Integrated with Local Wisdom - Edwin Pakpahan; Ramlan Silaban; Citra Sianturi (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study aims to identify the need for developing a redox reaction e-module based on Project-Based Learning (PjBL) integrated with ethnopedagogy in senior high school chemistry learning. The research addresses the gap between the Merdeka Curriculum’s emphasis on contextual, student-centered learning and the predominantly textbook-oriented instructional practices implemented in classrooms. A descriptive qualitative approach was employed at SMA Negeri 2 Percut Sei Tuan involving one chemistry teacher and 33 twelfth-grade students selected through purposive sampling. Data were collected through teacher interviews, student needs questionnaires, analysis of the Learning Objective Flow (ATP), and evaluation of existing textbooks using BSNP criteria. Quantitative data from questionnaires were analyzed using percentage calculations, while textbook feasibility was assessed using a five-point Likert scale. The findings indicate that 81.81% of students experience difficulties in understanding redox concepts, and learning remains largely expository and textbook-centered. Although the analyzed textbooks achieved a high feasibility score (89.36%, categorized as very suitable), they lack support for project-based, contextual, and ethnopedagogical integration. Furthermore, 96.96% of students expressed the need for interactive electronic learning media integrated with local wisdom. These results confirm the urgency of developing a structured e-module that aligns curriculum standards with active and culturally responsive learning. This study contributes theoretically by providing an empirical and systematic needs-analysis framework as a foundational basis for designing a PjBL-oriented redox e-module integrated with ethnopedagogy, addressing the limited research on culturally contextualized digital chemistry teaching materials.